Revolutionizing Supply Chains: Cloud-Based Analytics, Blockchain, and Security Solutions for Innovation (Global Journal of Computer Science and Technology, 2025)
The rapid evolution in technology advancements have resulted in massive transformation in the global supply chains industry These technologies bring in much needed innovative solutions that enhance efficiency transparency and security Cloud-based analytics blockchain technology and enterprise-level advanced security solutions are in the forefront of this evolving transformation Cloud-based analytics help supply chain stakeholders to make quick decisions based on data insight which are driven by real-time data processing with on-demand infrastructure Blockchain technology extends a decentralized and immutable ledger for better transparency traceability and security Using blockchain businesses can grow with decreasing fraud and enhancing trust between participants At the same time strong security measures safeguard valuable information and reduce the threat of cyberattacks maintaining the terms of data and confidentiality This paper explores the integration of these technologies to revolutionize how supply chains are designed and operated and displays a framework showcasing the proposed innovations to address contemporary challenges like inefficiencies frauds and cybersecurity issues and create sustainable yet adaptive supply chains of the future
Keywords: cloud-based analytics; blockchain techno-logy; supply chain innovation; data security; predictive insights; cybersecurity solutions